LEARNING DHARMA THROUGH NONFORMAL HINDU EDUCATION AMONG GENERATION Z IN DENPASAR CITY - Luh Dewi Pusparini (UHN I Gusti Bagus Sugriwa Denpasar, 2025)
Non-formal Hindu education plays a vital role in imparting the values of dharma beyond the formal school environment, especially in the modern era marked by the challenges of globalization and digitalization. This article explores the relevance and urgency of non-formal Hindu education for Generation Z in Denpasar City in maintaining cultural identity while fostering strong character. Generation Z, raised in the digital age, often struggles to understand and apply spiritual and local cultural values in daily life. Through pasraman (Hindu religious schools), cultural arts activities, and community-based religious rituals, non-formal Hindu education serves as a bridge between tradition and modernity. This article also identifies how non-formal Hindu education can strengthen morality, ethics, and a sense of responsibility among young people, while encouraging their creativity in facing modern life challenges. This study is expected to serve as a reference for Hindu communities in Denpasar City to further develop adaptive non-formal educational approaches that meet the needs of Generation Z without abandoning the core values of dharma.